'It is my decision, and it's really up to me. But they wanted me to do it': an exploration of choice in enrolling in a reengagement programme. Issue 11 (1st November 2016) - Thomas, Jeff; Dyment, Janet; Moltow, David; Hay, Ian
ABSTRACT: This study explores how choice to enter a reengagement programme was experienced and understood by students and staff. In seeking to understand choice, we sought to gain insight into one design element that is considered to be vital for effective reengagement programmes: namely, that they are voluntary or choice-based. We interviewed 12 students and 5 staff who were involved in a reengagement programme that was underpinned by philosophy of choice. Specifically, it was a mandate of the programme that students had to actively and voluntarily 'choose' to enter the programme. Analysis of the interviews revealed that it was not as simple as a student 'choosing' to enter the reengagement programme and then entering it. Rather, four main construct types emerged through the interviews that explained the ways in which choice was experienced by the students: (1) an opportunity for self-improvement, (2) an escape from the current situation, (3) a threat, for which the alternative would be a severe consequence, and (4) a nudge taken from a respected adult. Using a 'contexts-for-action' ecological model of agency, we seek to understand the construct types by exploring the complex factors that constrain or legitimize why, how, when, and with whom a student makes his/her 'choice'. The contexts that emerged in this study relate to the internal or external influences as well as whether the choice was proactive or reactive .